Assessment of the application and implementation of the Set (UN New YorkUS, 2015)
Reviews major developments that have taken place at the national, regional and multilateral levels in the field of competion law and policy, particularly since November 2010 when the 6th Conference was held.
Keywords: COMPETITION LAW